Trend of Uang Panai Researches: A Systematic Literature Review - Fajri AF, Muh Shadiqul (Universitas Pendidikan Ganesha, 2025)
One of the enduring traditions in the marriage practices of the Bugis ethnic group is the custom of uang panai. This tradition functions as a mandatory requirement that must be fulfilled prior to marriage negotiations. In Indonesia, a number of studies on uang panai have been published in journals indexed on Google Scholar. The present study aimed to examine the diversity of research approaches, designs, data collection and analysis techniques, as well as research locations in articles published between 2014 and 2024. Using the Publish or Perish (PoP) software, 102 articles were initially retrieved. To minimize bias and avoid duplication, the PRISMA protocol was applied, resulting in a final selection of 18 articles for analysis. The findings of this review led to two primary recommendations for future research. First, uang panai should be explored through ethnomethodological approaches to provide deeper insights into the experiences of grooms. Second, incorporating psychological and Islamic economics perspectives is suggested to further enrich the understanding of uang panai within both individual and socio-economic contexts.